Land market distortions and aggregate agricultural productivity: Evidence from Guatemala - Britos, Braulio; Hernandez, Manuel A.; Robles, Miguel; Trupkin, Danilo R. (International Food Policy Research Institute, 2020)
Farm size and land allocation are important factors in explaining lagging agricultural productivity in developing countries. This paper examines the effect of land market imperfections on land allocation across farmers and aggregate agricultural productivity. We develop a theoretical framework to model the optimal size distribution of farms and assess to what extent market imperfections can explain non-optimal land allocation and output in-efficiency. We measure these distortions for the case of Guatemala using agricultural census microdata. We find that due to land market imperfections aggregate output is 19% below its efficient level for both maize and beans and 31% below for coffee, which are three major crops produced nationwide. The regions with higher distortions show a higher dispersion in land prices and less active rental markets. We also find that the degree of land market distortions across locations co-variate with road accessibility and ethnicity and, in a lower extent, with education.